Pengaruh Environmental, Social and Governance Terhadap Kinerja Perusahaan: Studi Empiris pada Perusahaan Perbankan BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Salmawati; Linda Arisanty Razak; Asriani Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research impact of Environmental, Social, and Governance (ESG) factors on the performance of state-owned banking companies listed on the Indonesia Stock Exchange from 2019 to 2023. Given the growing importance of sustainable business practices, this study aims to analyze how ESG disclosures affect financial performance, specifically measured by Return on Assets (ROA). Utilizing empirical data, the research explores the relationship between these variables, emphasizing the significance of ESG in enhancing corporate reputation and overall financial health. The findings are anticipated to provide valuable theoretical insights and practical implications for companies striving to improve their ESG practices and financial outcomes.